PENGARUH LITERASI KEUANGAN DAN LITERASI DIGITAL TERHADAP KINERJA UMKM KOTA BIMA - Nurul Huda; Aliah Pratiwi; Aris Munandar (Universitas Dharmawangsa, 2023)
ABSTRACTThis study aims to see whether Financial Literacy and Digital Literacy affect the performance of MSMEs in Bima City. This research was conducted on MSMEs in Bima City. This study used a quantitative research method. The research object used is UMKM in Bima City. The number of MSMEs currently registered in Bima City is 5,868 MSMEs. The sampling method uses simple random sampling with a purposive sampling technique with the criteria of MSMEs that are still actively running their business in the year of research, MSMEs that have used recording applications in running their business and use social media as promotional media. Data collection techniques are carried out by means of observation, documentation, interviews, and questionnaires. The questionnaire was distributed to 100 MSMEs that have implemented digital applications. The data analysis technique uses the Classical Assumption Test, Multiple Linear Regression Analysis, t-test and F-test. The results show that financial literacy has no significant effect on the performance of UMKM in Bima City, while digital literacy has a significant effect on the performance of UMKM in Bima City.Keywords : Financial Literacy, Digital Literacy, MSME Performance